3-D simulation of arbitrary crack growth using an energy-based formulation – Part II: Non-planar growth. (March 2016) - Davis, B.R.; Wawrzynek, P.A.; Carter, B.J.; Ingraffea, A.R.
Highlights: Generalized energy-based method for predicting 3-D, non-planar crack growth. A new global implementation of the virtual crack extension method is used. A crack-extension function is determined to govern the incremental front evolution. Methodology reduces numerical bias and the need to prescribe crack advances. Predicted global non-planar and local front behavior, e.g. factory-roof formation. Abstract: The energy-based growth formulation and accompanying simulation technique introduced in Part I of this series is generalized in this work to predict arbitrary, mixed-mode, non-planar crack evolution. The implementation uses a novel basis-function approach to generate a crack extension expression, rather than relying on the local, point-by-point approach described in Part I. The basis-function expression dampens the effect of numerical noise on crack growth predictions that could produce numerically unstable simulation results. Two simulations are presented to demonstrate the technique's ability to capture both general non-planar behavior, as well as local mixed-mode phenomena, e.g. "factory-roof" formation, along the crack front.